Using Newspapers as Learning Media to Teach Reading Skills - Brigitta Septarini Rahmasari (Universitas PGRI Madiun, 2013)
For teachers the newspaper offers a special attraction. It has been called the living textbook and it lives up to that name. The newspaper can be used to enhance skills in reading. Critical thinking is the natural outgrowth of using a newspaper to learn. Unlike textbooks, which are several years outdated by the time they get into students' hands, the newspaper comes alive with information. The newspaper expands the curriculum with an unlimited amount of information to use as background for learning activities. These activities will help students improve their reading skills. These skills are how to find the main idea, how to increase vocabulary, how to find detail, how to make inference and how to find reference. They will employ many critical thinking skills as they are required to interact with the authentic material found in the newspaper.